Gut microbiota and targeted metabolomics of short-chain fatty acid reveals Qing-Re-Zao-Shi-Jian-Pi prescription on glucose and lipid metabolism in type 2 diabetic mice - Liu, Jing; Qin, Meng; Wang, Haidan; Ran, Yingzhuo; Shao, Xin (Frontiers in Nutrition, 2025)
BackgroundType 2 diabetes (T2D) is a group of metabolic disorders characterized by chronic hyperglycemia which caused by insufficient insulin secretion or defective insulin action. It has been found that the Qing-Re-Zao-Shi-Jian-Pi prescription (QRZSF) can effectively treat T2D in clinic, but the mechanism of action is unclear.MethodsThe T2D mouse model was constructed using combination of high-fat diet and intraperitoneal injection of Streptozocin. The levels of blood glucose, lipids, insulin resistance (IR), Interleukin-6 (IL-6), interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α) were detected, and the pancreatic tissue damage was evaluated by Hematoxylin and eosin (H&E) staining microscope. 16S rDNA high-throughput sequencing was performed to analyze the intestinal flora and LC-MS was used to detect the contents of short-chain fatty acids (SCFAs).ResultsThe fasting blood glucose, blood glucose during oral glucose tolerance test (OGTT), insulin, Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), Triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), Total cholesterol (TCHO), IL-1β, TNF-α were significantly decreased in QRZSF group compared with the model group. The damage of pancreatic tissue was improved, and the butyrate level was significantly increased. Besides, QRZSF group had a significant effect on intestinal flora profiling in T2D mice. Compared with the model group at the phylum level, the abundance of Proteobacteria, Chloroflexi, Fusobacteriota, Cyanobacteria were increased, while the abundance of Patescibacteria and Verrucomicrobiota were decreased in QRZSF group. At the genus level, the abundance of Anaerotignum, Akkermansia, Candidatus_ Saccharimonas were decreased, while the abundance of Acetatifactor and Bacteroides were increased. The possible mechanism is related to adjusting the abundance of gut microbiota and increasing Bacteroides and butyrate to reduce inflammation.ConclusionOur research showed that the QRZSF can correct the disorder of glucose and lipid metabolism, reduce the level of proinflammatory factors, improve IR and pancreatic tissue damage, regulate the diversity of gut microbiota, increase the content of butyrate in SCFAs, and then effectively prevent and delay the occurrence and development of diabetes. The study provides a new idea for the prevention and treatment of T2D with traditional Chinese medicine.